Laryngeal Framework Surgery in the Irradiated Neck: A Retrospective Matched Cohort Study. (October 2016) - Kubik, Mark; Rosen, Clark
Background: Laryngeal framework surgery (LFS) remains a cornerstone treatment in the management of glottic insufficiency. Traditionally, a history of radiation to the neck has been considered a relative contraindication to LFS. Methods: A retrospective matched cohort study was performed to study LFS outcomes in patients with and without a history of radiation. Variables studied included radiation specifics, surgical time, operative difficulty, complications, need for revision surgery, and Voice Handicap Index-10 (VHI-10) scores. Results: A total of 298 patients were studied. Fourteen patients with a history of neck irradiation were matched with 14 nonirradiated controls. No complications were encountered in the nonirradiated cohort. In the irradiated cohort, there were 2 minor wound complications and 1 admission for stridor treated medically. No cases of implant extrusion were observed. The VHI-10 scores were improved in both cohorts relative to preoperative baseline ( P = .001). Posttreatment VHI-10 scores were better in the nonirradiated cohort ( P = .03). There was no difference between cohorts with respect to complication rates, surgical time, surgical difficulty, length of stay, use of a surgical drain, or need for revision surgery. Conclusion: Laryngeal framework surgery is safe and associated with improved voice outcomes in patients with a history of neck irradiation.